La mobilisation de l’agriculture dans l’action paysagère de la région métropolitaine Cologne-Bonn - Louise Leconte (Projets de Paysage)
This article deals with the way in which landscape development in German metropolitan areas addresses the issue of agriculture in redefining the relationship between town and country. The findings come from an ongoing doctoral thesis and are the result of a case study of the Cologne-Bonn metropolitan based on the communication documents produced within the context of this landscape development as well as interviews with key players. The study focuses principally on the words and visual representations establishing a link between agriculture and landscapes. The development redefines the relationship between town and country in respect to several dimensions, and more specifically the promotion of the structural features of a landscape a cross between tradition and modernity and the concrete form given to the limits between built-up and open environments. Within this process farmers play a central role as the actors of a diversified local economy and as the producers and users of a space which is henceforth shared.